Knowledge Management in Transition Economies: Selected Key Issues and Possible Research Avenues - Michailova, Snejina; Sidorova, Elena (Organizations and Markets in Emerging Economies, 2010)
Most of the existing literature on knowledge and knowledge management has a Western or Japanese origin. While this literature provides important insights and findings, these may not necessarily be successfully replicable in other contexts and may lose some of their relevance when applied there. Such and similar observations have given a rise to a substantial number of knowledge management studies conducted in non-Western settings, among those transition economies. We highlight three particular challenges to the knowledge management literature in transition economies: moving beyond the extension of existing knowledge to instead developing contextualized and distinct knowledge; shifting from studying unidirectional knowledge transfer to examining multidirectional knowledge flows; and changing emphasis from studying knowledge transfer to studying knowledge creation.